Extracellular vesicles as a drug delivery system: A systematic review of preclinical studies - Escudé Martinez de Castilla, Pol; Tong, Lingjun; Huang, Chenyuan; Sofias, Alexandros Marios; Pastorin, Giorgia; Chen, Xiaoyuan; Storm, Gert; Schiffelers, Raymond M.; Wang, Jiong-Wei (Advanced drug delivery reviews, 2021)
[Display omitted] •Pros and cons and recent trends of EVs for drug delivery in animal disease models.•Quantitative analysis of the key parameters of EVs as drug delivery systems.•EVs have unique niches for RNA delivery and vaccine development.•Preclinical data of EVs as drug delivery systems to interpret with caution.•Lack of regulatory guidelines for clinical research of EVs as drug delivery systems. During the past decades, extracellular vesicles (EVs) have emerged as an attractive drug delivery system. Here, we assess their pre-clinical applications, in the form of a systematic review. For each study published in the past decade, disease models, animal species, EV donor cell types, active pharmaceutical ingredients (APIs), EV surface modifications, API loading methods, EV size and charge, estimation of EV purity, presence of biodistribution studies and administration routes were quantitatively analyzed in a defined and reproducible way. We have interpreted the trends we observe over the past decade, to define the niches where to apply EVs for drug delivery in the future and to provide a basis for regulatory guidelines.